Gastrointestinal Dissemination and Transmission of Staphylococcus aureus following Bacteremia - Kernbauer, Elisabeth (Infect Immun, 2014)
Mutations that alter virulence and antibiotic susceptibility arise and persist during Staphylococcus aureus bacteremia. However, an experimental system demonstrating transmission following bacteremia has been lacking, and thus implications of within-host adaptation for between-host transmission are unknown. We report that S. aureus disseminates to the gastrointestinal tract of mice following intravenous injection and readily transmits to cohoused naive mice. Both intestinal dissemination and transmission were linked to the production of virulence factors based on gene deletion studies of the sae and agr two-component systems. Furthermore, antimicrobial selection for antibiotic-resistant S. aureus displaced susceptible S. aureus from the intestine of infected hosts, which led to the preferential transmission and dominance of antibiotic-resistant bacteria among cohoused untreated mice. These findings establish an animal model to investigate gastrointestinal dissemination and transmission of S. aureus and suggest that adaptation during the course of systemic infection has implications beyond the level of a single host.